Dynamics of the Palang Pintu Tradition in Betawi Community Wedding Culture in Mampang Prapatan District 1990-2020 - Ramliza, Fahri; Nurhasanah, Ana; Ribawati, Eko (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research aims to determine the dynamics of the doorstop tradition in cultural studios in the Mampang Prapatan area around 1990-2020. The historical method was used in this study with a functional structural theory approach. The results of this research explain that the doorstop tradition has undergone various functional changes in the cultural life of the Betawi people in Jakarta. These changes include changes in cultural supporting instruments and the technical implementation of the doorstop tradition, although the values in this tradition have not disappeared and the implementation of this tradition has become a symbol that has a very meaningful meaning for Betawi people who want to get married. This tradition faces various challenges due to the development of the times and also the rapid development in Jakarta. Preservation is carried out by cultural practitioners, such as by introducing it to children and the general public so that this tradition is not lost in modern society.